2011
DOI: 10.33899/rden.2011.9135
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Assessment of Pre and Post Prosthetic Treatment of Partially Edentulous Patient (Radiographic Examination)

Abstract: Aims: This study investigates the condyle position in temporal fossa of completely and partially dentated patients pre and post prosthetic treatment, and compares between right and left condyles in both groups by radiographic Examination. Materials and Methods: Twenty two completely dentate patients (20-28) years old, and thirty partially dentate patients (35-65) years old meet the criteria of the study. For each patient a temporary removable acrylic partial denture was constructed. By using planmeca digital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The teeth have a crucial role in establishing a secure vertical and distal relationship between the mandible and maxilla. Additionally, they serve as guiding planes for the anterior and lateral movement of the jaw throughout the range of motion where the teeth are in contact (Shehab et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teeth have a crucial role in establishing a secure vertical and distal relationship between the mandible and maxilla. Additionally, they serve as guiding planes for the anterior and lateral movement of the jaw throughout the range of motion where the teeth are in contact (Shehab et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that tooth loss can greatly affect the TMJ morphology in several ways. The absence of posterior teeth, in particular, and the subsequent loss of the occlusal curve can disrupt the balance between adaptation and functional harmony, leading to impaired functionality (Shehab et al, 2011 ). Furthermore, the loss of teeth might have an impact on the inclination of the articular eminence through the process of remodeling (Shehab et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%